Tackling emerging outbreaks of infectious diseases: Preparedness for H1N1 Influenza in emergency department of a tertiary care institute of India - Chauhan, Anjali; Goel, Sonu; Singh, Amarjeet (International Journal of Infection Control, 2011)
With the threat of the emerging and reemerging infections (especially viral), it is time to gear up our health care facilities to tackle this menace. This short observational study conducted in the Out Patient Department of Emergency Department (ED), Post Graduate Institute of Medical Education and Research (PGIMER), Chandigarh in the month of August to October 2009 was done to analyze the efforts of preparedness of a pioneer institute of India PGIMER, Chandigarh when threatened by epidemic of H1N1 influenza. The information on existing policy, planning and it’s implementation regarding H1N1 were obtained. Data pertaining to infrastructural facilities, overcrowding and patient flow in the ED of PGIMER with respect to tackling of infectious outbreaks especially H1N1 influenza was collected. The data was also taken from laboratory registers of biochemistry and hematology labs present within the ED. The hospital census data pertaining to ED was obtained and analyzed. It was observed that the planning regarding pandemic influenza was initiated in PGIMER in August 2009, two months after first case of H1N1 was detected in Chandigarh. A multidisciplinary committee was constituted. Nodal officers were identified and channel of flow of information within the hospital and with the local health departments was established. A Standard Operating Procedure (SOP) was developed for managing H1N1 patients. PGIMER regularly updated its H1N1 plans in accordance with the guidelines issued by the Ministry of Health and Family Welfare (MOHFW). According to “hospital pandemic influenza planning checklist” by Centre of Disease Control, Atlanta, PGI fared well. Though the efforts were started late, but these were satisfactory. However, it was observed that ED had overcrowding, non- systematic patient flow, high patient load and high Average Length of Stay (AL S). The hospital ED was reasonably well prepared to tackle H1N1 situation except few lacunae at the policy and implementation level that needed to be addressed immediately.